JURIDICAL REVIEW OF CASES OF UNILATERAL TERMINATION OF EMPLOYMENT BASED ON LABOR LAW - Asya, Vanya Raghdatul; Riani, Ayundah; Lavidya, Viona (Gapenas Publisher, 2023)
This study examines cases of unilateral Termination of Employment (PHK) by employers. From this study, the objective was to find out the causes of Termination of Employment (PHK) by employers against workers in a normative juridical manner based on the Labor Law. The method used in this research is a normative juridical research method which is research based on legal aspects of legislation and through applicable laws. Termination of Employment (PHK) is the last resort taken by employers due to worsening working relations between workers and employers. Termination of Employment (PHK) is regulated in articles 158-169 of Law Number 13 of 2003 concerning Manpower. In this case, Termination of Employment (PHK) carried out by employers must comply with the provisions of the applicable law. If, indeed, it cannot comply with the regulations, it must be discussed in order to reach a consensus agreement between the employer and the worker, so that no party is harmed